Sharing the pain? Credit supply and real effects of bank bail-ins - Samuel da Rocha Lopes; Thorsten Beck; André F. Silva (European Banking Authority (EBA), 2018)
We analyze the credit supply and real sector effects of bank bail-ins by exploiting the unexpected failure of a major Portuguese bank and subsequent resolution. Using a matched firm-bank dataset on credit exposures and interest rates, we show that while banks more exposed to the bail-in significantly reduced credit supply at the intensive margin, affected firms compensated the tightening of overall credit with other sources of funding. Nevertheless, SMEs were subject to a binding contraction of funds available through credit lines and reduced investment and employment. These dampening effects are explained by the pre-shock internal liquidity position of smaller firms.
Keywords: E22; E24; E58; G01; G21; G28; G32; 330; banking crisis; debt assumption; corporate banking; credit rationing; SMEs; Investment; employment effect; Portugal; Bankenkrise; Schuldenübernahme; Firmenkundengeschäft; Kreditrationierung; KMU; Investition; Beschäftigungseffekt; Portugal